2022
DOI: 10.3390/brainsci12081034
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte, Monocyte-to-Lymphocyte, Platelet-to-Lymphocyte Ratio and Systemic Immune-Inflammatory Index in Different States of Bipolar Disorder

Abstract: The neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR) and systemic immune-inflammatory (SII) index, which provide a simple, rapid, inexpensive method to measure the level of inflammation, have been examined as potential inflammatory biomarkers of bipolar disorder (BD) in several studies. We conducted a case-control study recruiting 180 BD patients and 407 healthy controls. BD patients who met the inclusion criteria and were hospitalized due to BD at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…Finally, the secondary results of our study indicated decreasing PLR with age, and higher MLR in men compared to women. These sex-related results are in agreement with a study by Moosazadeh et al that showed similar sex differences in MLR [ 57 ], but were not found elsewhere [ 56 ]. On the other hand, the PLR decreased with age, which is not consistent with previously reported results [ 57 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Finally, the secondary results of our study indicated decreasing PLR with age, and higher MLR in men compared to women. These sex-related results are in agreement with a study by Moosazadeh et al that showed similar sex differences in MLR [ 57 ], but were not found elsewhere [ 56 ]. On the other hand, the PLR decreased with age, which is not consistent with previously reported results [ 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, our study was one of the few comparing both manic and depressive BD episodes to MDD, and also investigating the effects of type and duration of hospitalization, current psychotic, or suicidal features and psychiatric history on immune cell ratios. In addition, our sample size was comparable with several prior studies in the field [ 47 , 48 , 50 , 56 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The severity of BD-M has been shown to be strongly correlated with abnormal MLR values. 42 Monocytes are an important component of the innate immune response and play a regulatory role in the production and release of inflammatory factors (such as interleukin 1 and TNF-α). 43 Elevated serum TNF-α levels are also closely associated with high levels of aggression in patients with mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The MLR is calculated by dividing the monocyte count by the lymphocyte count. Increased MLR values can be associated with poor outcomes in various diseases, including cancer 18 . Systemic Immune-Inflammation Index (SII): Platelet Count × Neutrophil Count/Lymphocyte Count.…”
Section: Methodsmentioning
confidence: 99%